The Difference in Lower Limb Landing Kinematics between Adolescent Dancers and Non-Dancers. Issue 2 (June 2019) - Hendry, Danica; Campbell, Amity; Ng, Leo; Harwood, Annissa; Wild, Catherine
The high prevalence of lower limb overuse injuries among adolescent ballet dancers may be due in part to repetitive landings. This cross-sectional study compared how adolescent ballet dancers perform a drop-landing task in comparison to non-dancers in order to help understand injury mechanics. Fifteen adolescent female ballet dancers aged 11.9 ± 1.1 years and 17 non-dancers aged 10.9 ± 0.9 years each performed three single limb drop-landings from a 30 cm box. An 18-camera motion capture system (Vicon MX; Oxford Metrics, Oxford, UK; 250 Hz) and a force platform (Advanced Mechanical Technology Inc., Watertown, Massachusetts, USA; 2, 000 Hz) were used to collect lower limb joint angles in all three planes of motion and peak vertical ground reaction forces during the landing phase. These variables were compared for the two sets of participants using independent samples t-tests (p < 0.01). While the dancers landed with greater sagittal plane range of motion, this appeared to provide no mechanical advantage with no reduction in ground reaction force. Rather, the increased sagittal range of motion was coupled with increased coronal and frontal plane motion. This may place dancers at increased risk of injury.